On-the-road driving performance of patients with central disorders of hypersomnolence. (17th February 2021) - van der Sluiszen, N. N. J. J. M.; Urbanus, B.; Lammers, G. J.; Overeem, S.; Ramaekers, J. G.; Vermeeren, A.
Abstract: Introduction: Excessive Daytime Sleepiness is a core symptom of narcolepsy and idiopathic hypersomnia, which impairs driving performance. Adequate treatment improves daytime alertness, but it is unclear whether driving performance completely normalizes. This study compares driving performance of patients with narcolepsy and idiopathic hypersomnia receiving treatment to that of healthy controls. Methods: Patients diagnosed with narcolepsy type 1 (NT1, n = 33), narcolepsy type 2 (NT2, n = 7), or idiopathic hypersomnia (IH, n = 6) performed a standardized one-hour on-the-road driving test, measuring standard deviation of lateral position (SDLP). Results: Results showed that mean SDLP in patients did not differ significantly from controls, but the 95%CI of the mean difference (+1.02 cm) was wide (-0.72 to +2.76 cm). Analysis of subgroups, however, showed that mean SDLP in NT1 patients was significantly increased by 1.90 cm as compared to controls, indicating impairment. Moreover, four NT1 patients requested to stop the test prematurely due to self-reported somnolence, and two NT1 patients were stopped by the driving instructor for similar complaints. Conclusion: Driving performance of NT1 patients may still be impaired, despite receiving treatment. No conclusions can be drawn for NT2 and IH patients due to the low sample sizes of these subgroups. In clinical practice, determination of fitness to drive for these patients should be based on an individual assessment in which also coping strategies are taken into account.